(untitled) (Global Journal of Management and Business Research, 2019)
The objective conditions of a systemic crisis existed everywhere. Crises are inherent in capitalism, which produces them recurrently, each time deeply. It is not necessary to apprehend each crisis separately, but globally (Samir Amin, 2012). At the beginning of the year 2019, Venezuela is in the "global chaos": the crisis is the worse than the one known by the United States during the Great Depression of 1929-1933. My reflection in thisarticle revolves around the following questions: Can we say that the crisis in Venezuela is the logical consequence of the crises in the global economic system? Can we conclude that this crisis is the "systemic crisis" which shows that the capitalist system is in its phase of the ’old age’? Can we analyze as the result of the domination of a periphery by a center? Can we consider that this crisis is a permanent war of the North against the South? To give some answers, this article tries to analyze these questions by adopting the critical approach of Samir Amin as an anti-capitalist or antiimperialist theorist and philosopher.